Analysis of Western Kenya Isolates of Colletotrichum lindemuthianum Casual Agent of Bean Anthracnose using Pathogenicty and BOX-AIR Analysis - Mogita , Wilkister G.; Ochuodho , Julius O.; Gohole , Linet S. (African Journal of Education,Science and Technology (AJEST), 2013)
Anthracnose disease of common bean (Phaseolus vulgaris), caused by Colletotrichum lindemuthianum, is one of the major causes of yield losses. This pathogen is known to vary greatly in its pathogenicity challenging its control strategies which include, mainly development of resistant cultivars. The objective of this study was to investigate the pathogenic and genetic diversity among the C. lindemuthianum isolates collected from Bungoma, Kitale, Kakamega, Nandi, Busia, Kisii, Siaya of Western Kenya. One hundred and twenty two C. lindemuthianum isolates were obtained from bean pods with anthracnose symptoms collected from farmers’ fields during the two surveys. Virulence on a standard set of 12 common bean differential varieties and BOX-AIR analysis was used to asses the variability of the isolates. High levels of pathotypic (74pathotypes) were identified among 122 isolates, revealing that C. lindemuthianum is a highly diverse pathogen. Races 0 was the most frequent race and occurred in most regions. The most virulent races were less frequent and occurred in a single region only. 14 races broke the resistance of the most resistant cultivar G2333 indicating their high virulence. BOX-AIR analyzes performed on 60 of the 122 isolates revealed great genetic diversity, clustering the isolates into 8 groups. The races that clustered together were not the same nor from same region of collection. Due to the high virulence and genetic variation exhibited by C. lindemuthianum, breeding for more resistance genes appears to be the best option for developing cultivars with durable anthracnose resistance in Western Kenya.